1-[2,4,6-Trimethyl-3,5-bis(4-oxopiperidin-1-ylmethyl)benzyl]piperidin- 4-one - Rajesh, K.; Vijayakumar, V.; Sarveswari, S.; Narasimhamurthy, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the structure of the title compound, C(27)H(39)N(3)O(3), each of the (4-oxopiperidin-1-yl)methyl residues adopts a flattened chair conformation (with the N and carbonyl groups being oriented to either side of the central C(4) plane) and they occupy positions approximately orthogonal to the central benzene ring [C(benzene)-C-C(methylene)-N torsion angles 103.4 (2), -104.4 (3) and 71.9 (3)degrees]; further, two of these residues are oriented to one side of the central benzene ring with the third to the other side. In the crystal packing, supramolecular layers in the ab plane are sustained by C-H center dot center dot center dot O interactions.